Inclusion of host quality data improves predictions of herbivore phenology. Issue 8 (12th September 2018) - Abarca, Mariana; Larsen, Elise A.; Lill, John T.; Weiss, Martha; Lind, Eric; Ries, Leslie
Abstract: Understanding the correspondence between ambient temperature and insect development is necessary to forecast insect phenology under novel environments. In the face of climate change, both conservation and pest control efforts require accurate phenological predictions. Here, we compare a suite of degree‐day models to assess their ability to predict the phenology of a common, oligophagous butterfly, the silver‐spotted skipper, Epargyreus clarus (Cramer) (Lepidoptera: Hesperiidae). To estimate model parameters, we used development time of eggs and larvae reared in the laboratory at six constant temperatures ranging from 8 to 38 °C and on two host plants of contrasting quality (kudzu and wisteria). We employed three approaches to determine the base temperature to calculate degree days: linear regression, modified reduced major axis regression, and application of a generic base temperature value of 10 °C, which is commonly used in the absence of laboratory data. To calculate the number of degree days required to complete a developmental stage, we used data from caterpillars feeding on high‐ and low‐quality hosts, both in the field and in the laboratory. To test model accuracy, we predicted development time of seven generations of larvae reared in the field on the same host plants across 3 years (2014–2016). To compare performance among models, we regressed predicted vs. observed development time, and found that r 2 values were significantly larger when accounting for host plant quality. The accuracy of development time predictions varied across the season, with estimates of the first two generations being more accurate than estimates of the third generation, when ambient temperatures dropped outside the range in which development rate and temperature have a linear relationship. Overall, we show that accounting for variation in host plant quality when calculating development time in the field is more important than the choice of the base temperature for calculating degree days. Abstract : We evaluated a suite of degree‐day models for insect phenology developed and parameterized through various methodologies. To assess model performance we predicted the phenology of a multivoltine, oligophagous butterfly, silver‐spotted skipper, Epargyreus clarus (Lepidoptera: Hesperiidae), in the field over multiple years. We demonstrated that accounting for variation in host plant quality when calculating development time in the field was more important than the parameterization of the base temperature for calculating degree days.